A new species of Callianidea H. Milne Edwards, 1837 (Decapoda, Axiidea, Callianideidae) from the Pacific coast of Central America, with key to the genus - Hernáez, Patricio; Vargas, Rita (Zootaxa, 2013)
A new callianideid species, Callianidea mariamartae n. sp. is described from the Pacific coast of Costa Rica. The material is compared with the type description of C. laevicauda Gill, 1859 and C. typa H. Milne Edwards, 1837. Diagnostic features of the new species include a linea thalassinica very short, lateral margin of carapace with a distinct hepatic groove, accessory respiratory filaments unsegmented, outer uropodal ramus with strong longitudinal carinae. This is first record of the genus from eastern Pacific of Central America and third report of the family from world. A key for identification of the species belonging to the genus is provided in this document.